Selected Reading Strategies as Predictors of Reading Comprehension - muhamad bagus tajudin (Graduate Program, University of Islam Malang, 2020)
This research is intended to seeing the reading strategies as predictors of reading comprehension; the categories of reading strategy in this research are cognitive metacognitive compensation and social. This research was carried out to answer the problem is there any significant predictors of reading strategy to reading comprehension. This research used a quantitative approach with correlational research design. Correlational research design was used for investigating the contribution of independent variables to the dependent one. The students of Junior High School of Kediri ( MTS N I,II,III Kota Kediri ) were chosen as the subject of research with 730 populations of students. After being computed using accessibility sample, the sample is amount 319 students. Simple random sampling was used as the method and lottery was used as the media of taking sample.Keywords : Reading Strategies (cognitive, metacognitive, compensation, social), Reading Comprehension.Keywords: Reading Strategy, Reading Comprehension